Multiple regulatory effects of varicella-zoster virus (VZV) gL on trafficking patterns and fusogenic properties of VZV gH. - Duus, K M (1996)
Varicella-zoster virus (VZV) is an extremely cell-associated alphaherpesvirus; VZV infection is spread almost exclusively via cell membrane fusion. The envelope glycoprotein H (gH) is highly conserved among the herpesviruses. A virus-encoded chaperone, glycoprotein L (gL), associates with gH, and the gH:gL complex is required for gH maturation and membrane expression. We recently demonstrated that in the VZV system, the gH:gL complex facilitated cell membrane fusion and extensive polykaryon formation in transfected cells (K. M. Duus, C. Hatfield, and C. Grose, Virology 210:429-440, 1995). To further define the functions of the unusual VZV gL chaperone protein, we have performed a series of mutagenesis experiments with both gH and gL and analyzed the mutants by laser scanning confocal microscopy in a transfection-based fusion assay. We established the fact that immature gH exited the endoplasmic reticulum (ER) when coexpressed with either gE or gI and appeared on the cell surface in a patch pattern. A similar effect was observed on the cell surface with gH with a cytoplasmic tail mutagenized to closely resemble the vaccinia virus hemagglutinin cytoplasmic tail. Site-directed mutagenesis of the five gL cysteine residues demonstrated that four of five cysteines participated in the gL chaperone function required for proper maturation of gH. On the other hand, the same gL mutants facilitated transport of immature gH to the cell surface, where patching occurred. Studies of gL processing demonstrated that maturation did not require transport beyond the medial-Golgi; furthermore, gL was not detected in the outer cell membrane, nor was it secreted into the medium. Colocalization studies with 3,3'-dihexyloxa-cabocyanine iodide and N-(e-7-nitrobenz-2-oxa-1,3-diazol-4-yl-aminocaproyl)-D-erythro-sphingosine confirmed that gL was found primarily in the ER and cis/medial-Golgi when expressed alone. When all of these data were considered, they suggested a posttranslational gH:gL regulation model whereby the gL chaperone modulated gH expression via retrograde flow from the Golgi to the ER. In this schema, mature gL returns to the ER, where it escorts immature gH from the ER to the Golgi; thereafter, mature gH is transported from the trans-Golgi to the outer cell membrane, where it acts as a major fusogen.